Regular daily variations in satellite magnetic total intensity data - J. P. R. Turner; D. E. Winch; D. J. Ivers; R. J. Stening (Annales Geophysicae, 2007)
Regular magnetic daily quiet time (Sq) variations in total intensity of about 30 nT amplitude are determined in Universal Time (UT) from satellite magnetic field measurements. The CHAMP satellite traverses all hours of local time in 132 days and the Sq variations in total intensity are therefore calculated as an average over the 132 days for each hour of UT. Results are compared with the Sq daily variations in total intensity for the region above the ionosphere calculated from Malin's (1973) spherical harmonic analysis of the Sq Fourier coefficients for hourly mean value magnetic data from a global distribution of ground-based magnetic observatories. From the reasonable agreement between the two calculations, we conclude that low-Earth orbit satellites that traverse all hours of local time can determine Sq variations in total intensity above the ionosphere.